Computer data examination: the essence and procedural order - A. V. Kovalenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to clarifying the essence and procedural order of computer data examination in criminal proceedings. This type of examination, as defined by the Law of Ukraine No. 2137-IX dated 15.03.2022, is a novelty of criminal procedure legislation and requires theoretical elaboration. It is noted that the legislative consolidation of the types of examination should be determined by the need to establish specific procedural requirements for their conduct. It is specified that the direct object of such an examination is the audio-visual representation of computer data, which is defined as information contained in the storage device of an electronic computer in a format suitable for processing, transmission and interpretation by computer computing devices.